Tingkat Kesantunan Berbahasa Mahasiswa Universitas PGRI Palembang di Lingkungan Kampus - Aini, Dhea; Puspita, Yenny; Rukiyah, Siti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
The problem in this research is how the principles of language politeness are found in the speech of PGRI Palembang University students and how the language politeness of PGRI University Palembang students is based on the level of pragmatic parameters. This research aims to find out and describe the principles of language politeness found in the speech of PGRI Palembang University students and to find out and describe how language politeness of PGRI University Palembang students is based on the level of pragmatic parameters. The research method used is a qualitative descriptive method. The data collection technique used is the observation and documentation method. The research results that researchers obtained from the speech of PGRI Palembang University students in the campus environment, found that the speech of PGRI Palembang University students in the campus environment contained the principles of language politeness and a language politeness scale based on the level of pragmatic parameters.